A New Perspective on Gender: An Analysis of Surah Al-Ahzab Verse 35 with Muhammad Syahrur's Theory of Limits - Hasanah, Nur; Shofa, Ida Kurnia; Nidhom, Khoirun (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
Gender is a concept that describes the socially and culturally constructed differences in roles and responsibilities between men and women. In Islam, Surah Al-Ahzab verse 35 affirms gender equality in spiritual and moral aspects, emphasizing that both men and women have equal opportunities to achieve virtue. Muhammad Syahrur's Limit Theory also provides a new perspective on the flexibility of Islamic law in adapting gender norms to evolving social contexts. This study highlights the importance of understanding gender in building a more just and inclusive society while encouraging a more progressive interpretation of religious texts. This study examines gender equality in Surah Al-Ahzab verse 35 through the perspective of Muhammad Syahrur using the Limit Theory approach. This verse is considered a significant foundation that affirms the equality of roles between men and women in Islam. Employing a qualitative method and thematic interpretation approach, this study analyzes the minimum and maximum limits in Limit Theory to understand the implications of the verse on the concept of gender equality. The findings reveal that Muhammad Syahrur's interpretation offers a contextual approach relevant to universal values, while also providing critique against patriarchal views in traditional interpretations. This study emphasizes the relevance of the Qur'an as a guide supporting gender equality in various aspects of life. Gender merupakan konsep yang menggambarkan perbedaan peran dan tanggung jawab laki-laki dan perempuan yang dikonstruksi secara sosial dan budaya. Dalam Islam, Surah Al-Ahzab ayat 35 menegaskan kesetaraan gender dalam aspek spiritual dan moral, menunjukkan bahwa baik laki-laki maupun perempuan memiliki peluang yang sama dalam mencapai kebajikan. Pendekatan Muhammad Syahrur dengan Teori Limit juga memberikan pemahaman baru tentang fleksibilitas hukum Islam dalam menyesuaikan norma-norma gender dengan konteks sosial yang berkembang. Studi ini menyoroti pentingnya pemahaman gender dalam membangun masyarakat yang lebih adil dan inklusif, serta mendorong interpretasi yang lebih progresif terhadap teks-teks keagamaan. Penelitian ini mengkaji kesetaraan gender dalam Surah Al-Ahzab ayat 35 melalui perspektif Muhammad Syahrur dengan pendekatan Teori Limit. Surah tersebut dianggap sebagai salah satu landasan penting yang menegaskan kesetaraan peran laki-laki dan perempuan dalam Islam. Dengan menggunakan metode kualitatif dan pendekatan tafsir tematik, penelitian ini menganalisis batas minimum dan maksimum dalam Teori Limit untuk memahami implikasi ayat tersebut terhadap konsep kesetaraan gender. Hasil penelitian menunjukkan bahwa tafsir Muhammad Syahrur menawarkan pendekatan kontekstual yang relevan dengan nilai-nilai universal, sekaligus memberikan kritik terhadap pandangan patriarkal dalam tafsir tradisional. Kajian ini memperkuat relevansi Al-Qur'an sebagai pedoman yang mendukung kesetaraan gender dalam berbagai aspek kehidupan.